Well-Placed Acetabular Component Oriented Outside the Safe Zone During Weight-Bearing Daily Activities - Zheng, Nan; Hu, Xiangjun; Dimitriou, Dimitris; Dai, Kerong; Guo, Tao; Tsai, Tsung-Yuan (Frontiers in Bioengineering and Biotechnology, 2021)
Background: A comprehensive and thorough understanding of functional acetabular component orientation is essential for optimizing the clinical outcome after Total hip arthroplasty (THA). To quantify the functional acetabular anteversion and inclination of unilateral THA patients during walking and static standing and determine whether the functional acetabular orientation falls within the Lewinnek safe zone. Methods: Seventeen patients with unilateral THA received a CT scan and dual fluoroscopic imaging during level walking and static standing to evaluate in-vivo hip kinematics. The pelvic functional coordinate system of the 3D CT-based computer model was defined by the line of gravity and anterior pelvic plane (APP) to measure functional acetabular anteversion and inclination in different postures. The Lewinnek safe zone was used to determine the acetabular malposition during functional activities. Results: The THA side demonstrated an average of 10.1º (±9.6º, range -7.5º to 29.9º) larger functional anteversion and 16.0º (±9.2º, range -7.2º to 29.9º) smaller inclination than native hips during level walking. Functional acetabular anteversion in THA side during level walking and static standing was significantly larger than anatomical measurements (p<0.05). Acetabular orientation of most well-placed THA components anatomically in Lewinnek safe zone fell outside the safe zone during more than half of the gait cycle and static standing. Conclusion: The current study revealed an anatomically well-placed acetabular cup does not guarantee a well functional orientation during daily activities. The in-vivo mechanical performance and loading conditions of the THA component during other weight-bearing activities should be investigated in further study.